Efektivitas Model Contextual Teaching and Learning terhadap Motivasi Belajar Pendidikan Agama Islam Siswa Sekolah Dasar - Hidayati, Imalatul; Mufarrikoh, Zainatul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the effectiveness of the Contextual Teaching and Learning (CTL) model in improving elementary school students’ motivation to learn Islamic Education (PAI). The research employed a quantitative approach using a quasi-experimental pretest–posttest control group design. The participants were 43 fifth-grade students at SDN Dharma Camplong 2, Sampang Regency, divided into an experimental group applying the CTL model and a control group receiving conventional instruction. Data were collected through learning motivation questionnaires and classroom observations, and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The findings reveal that the implementation of CTL significantly increased students’ learning motivation. The experimental group showed an average motivation score improvement of 20.40 points, while the control group demonstrated an increase of only 5.40 points. Statistical analysis confirmed a significant difference between the two groups (Sig. = 0.000). Classroom observations further indicated higher levels of student participation, activeness, and enthusiasm in the experimental group. These results indicate that CTL is effective in fostering more meaningful and motivating Islamic Education learning experiences and can be considered an alternative instructional strategy for elementary schools, particularly in rural contexts.